2022
DOI: 10.2147/jir.s356551
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Transcriptomic Analysis and Experimental Validation Implicate a Central Role of STAT3 in Skin Barrier Dysfunction Induced Aggravation of Rosacea

Abstract: Objective Rosacea is a chronic inflammatory skin disease with high morbidity. Previous studies have described the contribution of skin barrier dysfunction (SBD) in the progression of rosacea, but the specific mechanism remains unclear. In this study, we aim to investigate the key genes that may involve SBD-mediated rosacea aggravation. Methods In this study, we evaluated the SBD patterns of rosacea based on the expression of 23 skin barrier-related genes (SBRGs) using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Memory T cells and B cells could quickly response to the triggers stimulated again 51,52 . Previous studies have found that CD4 + memory T‐cell infiltrations were significantly elevated in rosacea compared with healthy individuals 26 . This suggested that the increased memory T cells may contribute to a faster and more serious inflammatory response when being triggered by a series of pathogenesis conditions mentioned above.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Memory T cells and B cells could quickly response to the triggers stimulated again 51,52 . Previous studies have found that CD4 + memory T‐cell infiltrations were significantly elevated in rosacea compared with healthy individuals 26 . This suggested that the increased memory T cells may contribute to a faster and more serious inflammatory response when being triggered by a series of pathogenesis conditions mentioned above.…”
Section: Discussionmentioning
confidence: 93%
“…51,52 Previous studies have found that CD4 + memory T-cell infiltrations were significantly elevated in rosacea compared with healthy individuals. 26 This suggested that the increased memory T cells may contribute to a faster and more serious inflammatory response when being triggered by a series of pathogenesis conditions mentioned above. Macrophages were diffusely distributed in rosacea, which especially located in granulomatous areas and interfollicular areas of PPR, 47,53 and inflammatory reaction in rosacea could be alleviated by carvedilol through TLR2/KLK5/cathelicidin pathway in macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Barrier damage and changes in the production of epimmunome molecules (loss of sfT-SLP, high AMP level) are also suggested as drivers of papulopustular rosacea (PPR), which is localized to sebaceous SGR skin area. 4,[14][15][16][17] On the other hand, psoriasis, initiated rather by autoantigen presentation instead of outer epidermal/barrier challenges from the outside world, can be considered an inside-out dermatosis. 18 The objective of this study was (i) to determine the relative expression of cytokine-type epimmunome mediators in the three healthy skin regions, (ii) to calculate their absolute cytokine profiles, (iii) to better understand the function of the epimmunome profiles in the distinct regions by a literature search and (iv) to assess the most prominent epimmunome changes in outer epidermal challengedriven outside-in and inside-out skin diseases (AD, PPR and psoriasis respectively).…”
Section: Introductionmentioning
confidence: 99%
“…One such disease is atopic dermatitis (AD) which is initiated by barrier dysfunction followed by high IL‐25 and IL‐33 production and typically appears on dry GP skin region 12,13 . Barrier damage and changes in the production of epimmunome molecules (loss of sfTSLP, high AMP level) are also suggested as drivers of papulopustular rosacea (PPR), which is localized to sebaceous SGR skin area 4,14–17 . On the other hand, psoriasis, initiated rather by autoantigen presentation instead of outer epidermal/barrier challenges from the outside world, can be considered an inside‐out dermatosis 18 …”
Section: Introductionmentioning
confidence: 99%